Can Listed Companies Improve Corporate Performance by Improving the Quality of Accounting Information? (Asian Business Research, 2022)
The quality of accounting information of listed companies is an important factor affecting corporate performance.This paper selects 3460 listed companies in China from 2005 to 2019 as the research object, and studies therelationship between accounting information quality and corporate performance of listed companies. Throughempirical analysis, it is found that improving accounting information quality of listed companies can effectivelyimprove corporate performance. And the improvement of accounting information quality of non-state-ownedlisted companies is more significant than that of state-owned listed companies. This study provides a newperspective for Chinese listed companies to carry out accounting information quality management, and may alsocontribute to the healthy development of listed companies in other countries and regions.